Pengaruh Lingkungan Sosial Dan Keadaan Ekonomi Keluarga Terhadap Kesehatan Mental Remaja Di Kelurahan Aek Tampang - Replita Replita (Jurnal Kajian Gender dan Anak, 2020)
The social environment gives a lot of color to adolescents in Aek Urban Village, Padangsidimpuan City. This can cause the mental condition of adolescents often unstable. Teenagers in Aek Village look like they hang out with peers who don't have a strong religious spirit. Apart from environmental influences, it is also caused by the influence of the economic environment. The economic situation of families in this village is that many poor people are unable to respond to the needs and desires of their teenagers. This encourages teenagers to become naughty, and many are lazy to practice religious teachings